Self-propagating high-temperature synthesis of the high- current emission lanthanum and niobium contained ceramics; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Dolmatov O. Yu. Oleg Yurevich (2016, 2016)
Title screen